Implementasi Aturan Dasar dan AD/ART Berorganisasi Bagi UMKM Dpapahares Cafe di Sukaluyu Kecamatan Teluk Jambe Timur Karawang - Donant Alananto Iskandar; Adiguna Tumpuan; Naik Henokh Parmenas; Pranakusuma Sudhana; Modesta Titis Sadarum; Alan Adiansyah; Stefanus Ari Wibowo; Ignatius Ario Sumbogo (LPMP Imperium, 2023)
The group of housewives who play a role in contributing to the family's economy is the manager of the Dpapahares Café located at Perumnas Bumi Teluk Jambe, Karawang. This group of housewives has been under the guidance of PT Kalbe Farma's Corporate Social Responsibility since 2020. This training has produced various coffee drink products, side dishes, and home-cooked food. So far, Dpapahares Café has generated revenue of around IDR 500,000 on weekdays and IDR 1,000,000 on weekends. Unfortunately, in managing the Café business, the Chairman often faces internal conflicts caused by non-compliance with rules, and schedules, rejection of directions, and others. This problem makes Dpapahares Café not yet provide maximum profit and often experience internal conflicts. Even if the members pursue it seriously, this income can help their family's economy